Interaction of Notch and gp130 signaling in the maintenance of neural stem and progenitor cells - Kotasová, Hana; Procházková, Jiřina; Pacherník, Jiří (Cellular and molecular neurobiology, 2014)
Notch and gp130 signaling are involved in the regulation of multiple cellular processes across various tissues during animal ontogenesis. In the developing nervous system, both signaling pathways intervene at many stages to determine cell fate-from the first neural lineage commitment and generation of neuronal precursors, to the terminal specification of cells as neurons and glia. In most cases, the effects of Notch and gp130 signaling in these processes are similar. The aim of the current review was to summarize the knowledge regarding the roles of Notch and gp130 signaling in the maintenance of neural stem and progenitor cells during animal ontogenesis, from early embryo to adult. Recent data show a direct crosstalk between these signaling pathways that seems to be specific for a particular type of neural progenitors.
Keywords: Humans; Neurogenesis; nervové kmenové buňky; zvířata; signální transdukce; Cytokine Receptor gp130; Receptors, Notch; cytokinový receptor gp130; Animals; interakce mezi receptory a ligandy; lidé; Receptor Cross-Talk; receptory Notch; Neural Stem Cells; neurogeneze; Signal Transduction